Associação da insegurança alimentar e nutricional com indicadores sociodemográficos, antropométricos, bioquímicos e de consumo alimentar em escolares de um munícipio sul mineiro - Silva, Amanda Aparecida Oliveira Da (2024)
Food and Nutrition Insecurity/FNI can be characterized as the absence or reduced access to food in quantity and sufficient quality for the development of individuals. This study aimed to evaluate the FNI and associated factors in schoolchildren in the municipality of Poço Fundo, Minas Gerais, Brazil. This was a cross-sectional study with 178 children aged 6 to 9 years. Information on FNI, lifestyle, food consumption, and sociodemographic, anthropometric, and biochemical profiles were collected using standardized protocols. The data were presented using descriptive and inferential analyses and univariate and bivariate analyses. SPSS version 25.0 and Jamovi version 2.3 software were used. All variables with a significance level of p<0.20 were subjected to the logistic regression model, and a statistical significance level of p<0.05 was considered for the other analyses. The FNI was 29.2% (n=52) in the sample evaluated. According to the regression analysis, individuals with a monthly family income of up to 1 minimum wage, who had experienced a change in post Covid-19 income, and who consumed snack foods/instant noodles were more likely to experience the outcome (IAN). On the other hand, beneficiaries of the government program, who consumed fresh fruits and ate four meals a day, had a lower risk of FNI. The receiver operating characteristic (ROC) curve indicated the excellent ability of the logistic regression model to classify the variables (specificity: 0.862; sensitivity: 0.635 and area under the curve: 0.897). Notably, unfavorable socioeconomic factors and food consumption markers were associated with FNI in schoolchildren.